Beyond Authenticity? Humanism, Posthumanism and New Organization Development. (11th March 2013) - Bryant, Melanie; Wolfram Cox, Julie
<x xml:space="preserve">Abstract</x> In recent debates, the relevance of traditional objectivist organization development (OD) approaches has been questioned in terms of their appropriateness for contemporary organizations. A new OD has emerged wherein change is viewed as a socially constructed process and where there are multiple rather than singular authentic possibilities. We explore these possibilities by drawing on employees' discussions of how they manage conflicting interpretations of organizational change. Using the example of emotional labour, we compare traditional and new OD approaches in terms of how they view authenticity and then discuss posthumanist analysis, in which authenticity (or lack thereof) is no longer of focal concern. In particular, under traditional OD, where authenticity can be 'discovered', the need to negotiate multiplicity and to downplay 'negative' responses is a problem to be addressed. Under new OD such multiplicity becomes data for dialogue and discussion of future potentials. In contrast, a posthumanist analysis, while relational, neither reframes nor tempers authenticity but decentres the very notion of autonomy on which authenticity is based. The social constructionism of new OD is recast and implications for theory and intervention are discussed.